Sintesis Senyawa Heksapeptida Siklik Analog Pipecolisporin (Pro-Lys-Pip-Trp- - Dwi Maulidani Fadhlan; Nety Kurniaty; Rani Maharani (UNISBA Press, 2023)
Pipecolisporin compounds isolated from the fungus Nigrospora oryzae from theroots of Triticum sp. is one of the compounds that has potential as an antimalarial with its activity against Plasmodium falciparum of 3.21 μM. The modification of the amino acid sequence to Pro-Lys-Pip-Trp-β-Ala-Phe aims to determine the best arrangement of pipecolisporin analogues as antimalarials. Analogues of pipecolisporin linear hexapeptide compounds were synthesized using the solid phase peptide synthesis (SPPS) method with the use of buffers in the form of 2-chlorotrityl chloride resins, Fmoc and Boc protective groups, and DIC, Oxyma, Dipea coupling reagent solutions. The synthesis results were obtained as much as 9 mg and then characterized using mass spectroscopy with a peak m/z of 959.5246 [M]. Analogues of linear pipecolisporin hexapetide compounds were successfully cyclized using the solution phase peptide synthesis (LPPS) method with the use of DIPEA, HATU, DCM reagent solutions. The synthesis results were characterized using mass spectroscopy with an m/z peak of 743.78 [M+H]+. Senyawa pipecolisporin hasil isolasi jamur Nigrospora oryzae dari akar Triticum sp. merupakan salah satu senyawa yang berpotensi sebagai antimalaria dengan aktivitasnya terhadap Plasmodium falciparum sebesar 3,21 μM. Modifikasi urutan asam amino menjadi Pro-Lys-Pip-Trp-